Enhanced Anticorrosion Properties through Structured Particle Design of Waterborne Epoxy-Styrene-Acrylate Composite Emulsion - Kai Zhang (MDPI AG, 2021)
In order to develop a waterborne epoxy-styrene–acrylate composite latex with a better stability and anticorrosion resistance, a novel synthetic approach has been proposed. First, modified by methyl acrylic, epoxy resin containing terminal C=C double bonds was successfully synthesized, where epoxide groups were partially retained. Then, by structural design and multi-stage seed emulsion copolymerization, a stable waterborne epoxy-styrene-acrylate composite latex composed of a modified epoxy resin acrylate polymer as the core, inert polystyrene ester as the intermediate layer, and carboxyl acrylate polymer as the shell was successfully fabricated. The structure of the obtained latex was characterized by fourier transform infrared (FTIR) and transmission electron microscopy (TEM). The stability of the composite latex was tested based on the wet gel weight, Zeta potential, and storage stability, and the corrosion resistance of the composite latex films was analyzed by electrochemical measurements and salt spray tests. The thickness of each layer of the composite latex was calculated by the temperature random multi-frequency modulation DSC (TOPEM-DSC) technique. In addition to the successful emulsion copolymerization that occurred between the modified epoxy resin and acrylate monomer, the presence of carboxyl groups in the obtained latex was evidenced, while the epoxide groups were partially retained. The anticorrosion resistance and stability of the multilayer composite latex with the intermediate layer are better than that of the conventional core-shell latex. The outstanding stability and corrosion resistance is attributed to the multilayer core-shell structure. The TOPEM-DSC approach can accurately determine the thickness of the intermediate layer in the multilayer core-shell particles and is a new strategy for characterizing the core-shell structure of polymer particles with a similar monomer composition.